TINJAUAN YURIDIS PASAL 345 KUHP MENGENAI TINDAKAN MENDORONG ORANG LAIN UNTUK BUNUH DIRI: TINJAUAN YURIDIS PASAL 345 KUHP MENGENAI TINDAKAN MENDORONG ORANG LAIN UNTUK BUNUH DIRI - Anak Agung Linda Cantika, Anak Agung Linda Cantika; I Kadek Agus Merta Adnyana (Cattleya Darmaya Fortuna, 2024)
The qualification for the act of ending one's own life or suicide in the criminal code is stipulated in Article 345 of the Criminal Code, stating: